Effects of Dietary Rucah Fish Meal on the Performance and Protein Efficiency Ratio of Local Chickens - Nurhayati Nurhayati; Farhan Dwi Ramadan; Faizah Jum’atul Hasanah; Jevi Mufit Hidayani; Nelwida Nelwida; Lisna Lisna; Fauzan Ramadan; Filawati Filawati (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
This study determined the effects of dietary Rucah fish meal on the performance and protein efficiency ratio of local chickens. Two hundred day-old local chicks (initial BW: 42.4 g; CV: 7.48%) were raised for eight weeks and assigned to a completely randomized design (CRD) consisting of five dietary treatments with four replicates of 10 birds each. The treatments were as follows: T0 = diet containing 12% Rucah fish meal, T1 = diet containing 14% Rucah fish meal, T2 = diet containing 16% Rucah fish meal, T3 = diet containing 18% Rucah fish meal, and T4 = diet containing 20% Rucah fish meal. Feed intake, body weight gain, feed conversion ratio, protein intake, protein efficiency ratio, slaughter weight, and carcass percentage were also recorded. Data were analyzed using analysis of variance (ANOVA), and parameters showing significant effects were further analyzed using Duncan’s multiple range tests. The inclusion of Rucah fish meal from 12% to 20% did not significantly affect (P>0.05) any of the measured parameters, including feed intake, body weight gain, feed conversion ratio, protein intake, protein efficiency ratio, slaughter weight, and carcass percentage. Overall, the results of this study indicate that Rucah fish meal can be included in local chicken diets at levels up to 20% without any adverse effects on growth performance, protein utilization, or carcass yield, demonstrating its potential as a sustainable and locally available alternative protein source for poultry production.